Development of conditions for entry of two strikers into water and achieving parallel motion in it by them - Burkin, Viktor V.; Diachkovskii, Alexei S.; Ishchenko, Aleksandr N.; Skibina, N. P.; Faraponov, Valery V.; Chupashev, Andrey V. (Journal of engineering physics and thermophysics)
This article presents the results of external ballistic investigations of motion in the air of supercavitating strikers cannon-launched in a group, and a gas-dynamical picture of flow past two strikers in the chamber of an aerodynamic installation. Mathematical simulation of the process of flow past two strikers has been carried out, and their aerodynamic coefficients have been calculated The conditions for cannon-launching of a group of supercavitating strikers have been determined that provide for their motion along the aerodynamic portion of the route and their subsequent entry into water with an angle between the longitudinal axes of strikers, at which their motion is stable.